Choeronycteris mexicana in Guatemala: temporal occurrence, feedinghabits and reproductive activity - José Octavio Cajas-Castillo; Cristian Kraker-Castañeda; Jorge E. López-Gutiérrez; Sergio G. Pérez-Consuegra; Ana L. Grajeda-Godínez (Revista Mexicana de Biodiversidad)
During 2003, 2007, 2008 and 2010, bat assemblages were studied at different dry valleys in Guatemala. Ten individuals of Choeronycterismexicana (7 females and 3 males) were captured almost exclusively during the dry season. Pollen of columnar cacti (Stenocereus pruinosus andPilosocereus leucocephalus) and Ceiba aesculifolia were found in samples recovered from hair. Remains of insects were recovered from fecessamples of one individual. Reproductive females and a juvenile were captured between March and June of the different years. The capturescoincided with the blooming of columnar cacti flowers, and with the presence of Leptonycteris yerbabuenae. Our data suggest that C. mexicana isa seasonal visitant at sub-humid biological corridor in Guatemala.